Fluorescent phenothiazine-triazine donor-acceptor conjugates by facile consecutive nucleophilic displacement – Color tuning by substitution and protochromicity. (October 2022) - Kloeters, Laura N.; May, Lars; Tengen, Bärbel; May, Lea; Müller, Thomas J.J.
Abstract: A series of phenothiazine-triazine chromophores is prepared starting from brominated phenothiazine in a one-pot fashion by twofold nucleophilic substitution on cyanuric chloride. The title compounds show high fluorescence quantum yields in solution and in the solid state spanning a color range from deep blue to red by modulating the acceptor strength of the triazine moiety. Electron deficient substituted triazine chromophores exhibit a strong charge transfer character as shown by solvatochromism studies and small singlet-triplet energy gap making them interesting-candidates for thermally activated delayed fluorescence (TADF). Protonation of an electron rich triazine chromophore resulted in shifted spectral emission and showed in one case the formation of complementary emission colors and white light formation. Thus, by substitution of the triazine spectral emission color can be fine-tuned and specific photophysical properties like TADF and white light emission can be addressed. Graphical abstract: Image 1 Highlights: The urgency and relevance of our contribution for a broad readership of organic, dye and materials chemists are justified by the following aspects: 1) Our general approach is the concept of modular one-pot syntheses of functional dyes, predominantly fluorophores. Phenothiazine-triazine chromophores can be readily accessed by a consecutive sequence of nucleophilic displacements starting from a 3-bromo phenothiazine donor, cyanuric chloride, and alcohol or amine nucleophiles. 2) The title compounds are intensively luminescent in solution and in the solid state with a color range from deep blue to red by modulating the acceptor strength of the triazine moiety. 3) The pronounced emission solvatochromism as well as small singlet-triplet energy gaps in the excited states make them interesting candidates for TADF systems. 4) Protonation of an amino substituted triazine chromophore results in the formation of complementary emission colors and white light formation in a certain pH range. 5) The UV/Vis absorptions are very well reproduced by (TD)DFT calculations and allow a rationalization of the photophysical characteristics.